Effects of three-dimensional coating interfaces on thermo-mechanical stresses within plasma spray thermal barrier coatings - Kyaw, Si; Jones, Arthur; Jepson, Mark A.E.; Hyde, Tom; Thomson, Rachel C. (Elsevier, 2017)
It has been acknowledged that stresses within a thermal barrier coating (TBC) and its durability are significantly affected by the coating interfaces. This paper presents a finite element approach for stress analysis of the plasma sprayed TBC system, using three-dimensional (3D) coating interfaces. 3D co-ordinates of the coating surfaces were measured through 3D reconstruction of scanning electron microscope (SEM) images. These co-ordinates were post processed to reconstruct finite element models for use in stress analyses. A surface profile unit cell approach with appropriate boundary conditions was applied to reduce the problem size and hence computation time. It has been shown that for an identical aspect ratio of the coating interface, interfacial out-of-plane stresses for 3D models are around twice the values predicted using 2D models. Based on predicted stress development within the systems, possible crack development and failure mechanisms of the TBC systems can be predicted.